Brain lesion characteristics in Chinese multiple sclerosis patients: A 7‐T MRI cohort study - Lei Su; Zhe Zhang; Chenyang Gao; Ai Guo; Mengting Zhang; Xiaoyu Shi; Xinyao Liu; Tian Song; Wangshu Xu; Huabing Wang; Joseph Kuchling; Jing Jing; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective Prevalence, susceptibility genes, and clinical and radiological features may differ across different ethnic groups of multiple sclerosis (MS). We aim to characterize brain lesions in Chinese patients with MS by use of 7‐T MRI. Methods MS participants were enrolled from the ongoing China National Registry of Neuro‐Inflammatory Diseases (CNRID) cohort. 7‐T MRI of the brain was performed. Each lesion was evaluated according to a standardized procedure. Central vein sign (CVS) and paramagnetic rim lesions were identified. The characteristics of lesions at patient‐level and at lesion‐level from previous 7‐T MRI literature were also summarized. Results We included 120 MS patients. Their mean (SD) age was 34.6 (9.4) years. The female‐to‐male ratio was 1.7:1 and mean disease duration of patients with MS was 5.5 ± 6.1 years. The median EDSS score was 2 (range, 0–8). A total of 8502 lesions were identified with a median lesion count of 45 (IQR, 18–90) (range, 2–370). The median (IQR) percentage for these special locations were as follows: cortical lesions (CLs) 2.7% (0%–5.7%), juxtacortical lesions 16.2% (7.8%–25.7%), periventricular lesions 30.2% (17.2%–38.7%), and infratentorial lesions 5.8% (0.4%–11.9%). CLs occurred in 70 (58%) patients, accounting for only 443 (5%) of the total lesions. Out of the 443 CLs, 309 (69.8%) were leukocortical lesions. CVS appeared in 5392 (63%) lesions from 117 (98%) patients. 1792 (21%) lesions and 104 (87%) patients exhibited a paramagnetic rim. Interpretation Our study elaborated on the lesion features of Chinese patients with MS by use of 7‐T MRI. Lesion burden is heavy in Chinese patients with MS. The median lesion count and proportion of PRL are high. The reported heavy lesion burden calls for ramping up regional and global efforts to care for MS patients. The management and research of Chinese population with MS needs to be further strengthened.